If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = 4x + -12 Reorder the terms: -10 + 6x = 4x + -12 Reorder the terms: -10 + 6x = -12 + 4x Solving -10 + 6x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -10 + 6x + -4x = -12 + 4x + -4x Combine like terms: 6x + -4x = 2x -10 + 2x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 + 2x = -12 + 0 -10 + 2x = -12 Add '10' to each side of the equation. -10 + 10 + 2x = -12 + 10 Combine like terms: -10 + 10 = 0 0 + 2x = -12 + 10 2x = -12 + 10 Combine like terms: -12 + 10 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| x/6+(-52)=-84 | | x+18=32 | | -3(2x-3)=19 | | 58x-124=234 | | -5(-4-12n)=-7(1-9n) | | X-6=-5+9 | | y+64=6 | | (x^2-1)-2x^2=0 | | -7y+3=-17 | | 4(y+1)+y=8(y-1)+6 | | 8x-4=6x+10 | | -1+7(12b-5)=11(5+7b) | | -39+t=30 | | -7(1+3x)=-7(x+9) | | 3(9x-1)=-30 | | 9z=12-30 | | x^2-13x-38=0 | | 2/5w-3/2=-7/3 | | 12n3+8x2-6n/2x2 | | 4(v+3)=-5v-33 | | I/(2+I) | | f=9/5c*30+32 | | 6x-16=40 | | 9(-3r-5)=-11(1+4r) | | -28.7=-3.1+u/2 | | -6+16y=9 | | (6x-7)=71 | | 6-3x=5x-10x+15 | | c=5/9(30)(f-32) | | 9d-3=5d-9 | | -7/2a=21 | | 5/3x^2+6/x |